Profil critical thinking dalam proses pembelajaran biologi di SMA Kabupaten Purbalingga - Yohana Alifia Prasetya; Mufida Nofiana (Bio-Pedagogi : Jurnal Pembelajaran Biologi, 2025)
ENMerdeka Curriculum requires students to possess 21st-century competencies, one of which is critical thinking, categorized under learning and innovation skills. This study aimed to analyze the profile of critical thinking and the role of biology learning processes in empowering the dimensions of critical thinking among senior high school students in Purbalingga Regency. To date, there has been no mapping in these schools regarding how biology learning contributes to strengthening critical thinking dimensions. The analysis adopted Ennis's five aspects of critical thinking: providing simple explanations, building basic skills, drawing conclusions, providing further explanations, and setting strategies and tactics. This research employed a quantitative descriptive approach with data collected through observation, critical thinking tests, interviews, and documentation. The population included 16 high schools (ten public and six private). A cluster random sampling technique was implemented, with the sample size taken as 20% of the total population. The results revealed that students' critical thinking ability in these schools was at a moderate level, with an average achievement rate of 45.6%. The highest average percentage was in the aspect of providing further explanations (57.3%), and the lowest was in providing simple explanations (41.2%). A mismatch between teaching modules, learning processes, and evaluation questions in classroom implementation was identified as the main issue affecting students' critical thinking development. Teachers play a crucial role in designing learning strategies that train students to think logically, analytically, and reflectively.IDKurikulum merdeka menuntut siswa untuk memiliki kompetensi abad 21, salah satunya critical thinking yang termasuk dalam kompetensi learning and innovation skills. Penelitian ini bertujuan untuk menganalisis profil critical thinking dan peran proses mata pelajaran biologi dalam memberdayakan dimensi critical thinking pada siswa SMA di Kabupaten Purbalingga. Di SMA Kabupaten Purbalingga belum pernah dipetakan terkait peran mata pelajaran Biologi dalam memberdayakan dimensi critical thinking. Analisis dimensi critical thinking menggunakan lima aspek berpikir kritis menurut Ennis: memberikan penjelasan sederhana, membangun keterampilan dasar, menyimpulkan, memberikan penjelasan lanjut, dan mengatur strategi dan taktik. Penelitian ini menggunakan pendekatan deskriptif kuantitatif dengan teknik pengumpulan data observasi, tes critical thinking, wawancara, dokumentasi. Populasi penelitian terdiri dari 16 SMA (10 SMA Negeri dan 6 SMA Swasta). Teknik pengambilan data cluster random sampling. Jumlah sampel diambil 20% dari jumlah populasi. Hasil penelitian menunjukkan bahwa kemampuan berpikir kritis siswa di SMA Kabupaten Purbalingga berada pada kategori sedang dengan persentase rata-rata capaian 45,6%, persentase rata-rata tertinggi pada aspek memberikan penjelasan lanjut (57,3%) dan persentase rata-rata terendah pada aspek penjelasan sederhana (41,2%). Ketidaksesuaian antara modul ajar, proses pembelajaran, dan soal evaluasi pembelajaran dalam implementasinya di kelas menjadi permasalahan utama dalam pencapaian critical thinking siswa. Guru berperan penting dalam merancang strategi pembelajaran yang melatih siswa berpikir logis, analitis, dan reflektif.